Epigrafi Islam: Telusuran Sejak Orde Baru Hingga Kini - Tawalinuddin Haris (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
Studies in Islamic Epigraphy in Indonesia had been conducted by many national and international experts. This study focus on researchs of incriptions that have not yet reviewed or the researchs that correcting/criticize the previous research. The study limited to research discussion about Islamic inscription in Indonesia since the new order era until the beginning of the 21st century. This effort has be done as assessments to furnish the report that has been done by Uka Tjandrasasmita in articles investigation the acts of paleontologists Islam in Indonesia. This research concluded that there are many uniqueness that was found in Indonesian Islamic inscription that the possibility of not there are in other countries.Keywords: Epigraphy, Puslitarkenas